URBAN REALISTIC PROSE: NOVELS BY KARAVELOV AND CHERNYSHEVSKY (Philological Studies, 2019)
The role of Karavelov in Serbian culture and literature was investigated as one of the pioneers of social realism and one of the main founders of the Serbian realistic narrative and criticism. In Serbian literature, Karavelov introduces new themes, new stylistic and rhetorical means and reveals new possibilities of narration.It was investigated originality of Karavelov's novel in regards to the novel of N. Chernishevski What to do? An unfinished novel Is it the fault of destiny? represents the first literary work on Belgrade's life in Serbian realism and certainly the most importantwith the theme of social life after the novel by Jakov Ignjatovic. Patriarchal culture models that considerably shape urban, on the background of Central European and Western European civilizational influences, were also considered.
Keywords: Karavelov, realism, urban prose, Chernyshevskiy, patriarchic culture, Serbian literature